Analisis Debit Banjir Rencana Menggunakan Metode Rasional di Jalan Karah, Kecamatan Karah, Kota Surabaya - Bagaskara, Femas Putra; Wulandari, Esti; Safitri, Dika Ayu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Flooding along Karah Street, Karah District, occurs due to the insufficient capacity of the drainage channel to accommodate surface runoff. This study aims to analyze the existing capacity of the drainage system and to evaluate its adequacy against the design discharge based on hydrological data using HEC-RAS software. The research method employed is descriptive quantitative, consisting of hydrological and hydraulic analyses. The data include maximum daily rainfall, topographic conditions, and field observations of the drainage channel. The hydrological analysis determines design rainfall using the Gumbel distribution and calculates runoff discharge using the rational method. The hydraulic analysis is performed by modeling channel capacity with HEC-RAS to determine whether the cross-section can accommodate the design discharge. This study is expected to provide an overview of the current condition of the Karah drainage system and serve as a basis for planning improvements to increase channel capacity and reduce flood potential in the area.